SEMANTICS AND WORD FORMATION OF DERIVATIVE NOUNS IN THE CONTEXT OF SECONDARY NOMINATION - Yelmuratova, Sayora Abylaevna (SCIENCE and SOCIETY, 2026)
The article examines derived concrete nouns as a means of secondary nomination of objects in modern Russian. The word-formation mechanisms of their creation are analyzed, and the main semantic types of secondary nomination as well as the functional characteristics of these units are identified. Special attention is paid to the role of the motivation of derived nouns and to their participation in shaping the object-based picture of the world.